Ecomorfologia e uso de recursos alimentares : relações inter e intraespecíficas da ictiofauna associada a bancos de macrófitas aquáticas. - Prado, Aline Vanessa Rosa do (2015)
The ecomorphology is the study of relationships between morphological characters and their ecological attributes, whose goal is to understand the responses of organisms to environmental challenges through comparisons of such characters variations standards. The use of food resources for fish is as diverse as the items available in the aquatic environment, and this fact may be due to morphological diversity related to the acquisition of food. Thus, hypotheses were tested: i) the morphology explains the variations between species in the diet of fish ii) intraspecific morphological diversity is related to the amplitude of ecological niches exploited by species, so that species that feed on higher variety of resources have greater variation in body shape over those specialized in resource consumption. Fish were collected in banks of aquatic macrophyte Eichhornia azurea and Eichhornia crassipes in lentic environments of the floodplain of the upper Paraná River, Brazil. The ecomorphology was evaluated by indices ecomorphological and diet through analysis of stomach contents. The morphology data were ordered by Principal Component Analysis to identify patterns of variation and for the classification of species in trophic guilds we used the Alimentary Index from the diet data. The Mantel test was used to examine the association between diet and interspecific morphology. For the determination of intraspecific morphological diversity were calculated average distance between the specimen and the centroid of the population, which indicates the degree of occupation of space ecomorphological; the average distance to the nearest neighbor, which indicates the degree of packing of the specimens in ecomorphological space; and the standard deviation from average distance to the nearest neighbor, which indicates the packaging evenness of the specimens in ecomorphological space. These measures were based on the calculation of the Euclidean distance. The variation trend of observed values such as the range of distances ecological niches was analyzed by simple linear regression. A total of 506 fish were measured and had their stomach contents analyzed. The results show the relationship between diet and interspecific morphology, confirming the first hypothesis. However, the amplitudes of morphological and trophic changes intraspecific were not significantly related, rejecting the latter. The morphology of the species explains the use of food resources and the eco-morphology is a fundamental tool for this, but probably for the better understanding of the relationship morphology / diet should be used analysis of abundant resources.